Evaluation of Pharmacological Potential of Tamarindus indica in Streptozotocin Induced Diabetic Rats - Bibekananda Meher (Current Research in Pharmaceutical Sciences, 2017)
Diabetes mellitus is associated with dyslipidemia. The present study was carried out to evaluate the antidiabetic and hypolipidemic potential of hydro-alcoholic and aqueous seeds extract of Tamarindus indica on Streptozotocin induced diabetic rats. In oral glucose tolerance test the blood glucose level was significantly (P<0.05) controlled in 0-90 min after glucose administration in normal and streptozotocin induced diabetic rats. The blood glucose level of Streptozotocin induced diabetic rats were determined at 0,7,14 days of treatment after 14 days of treatment blood glucose levels were significantly (P<0.05) decreased. Hydro-alcoholic seeds extract at the dose of 200 mg/kg significantly increased the serum insulin level. Tamarindus indica seeds extracts at all the dose level 100 and 200 mg/kg, after 14 day days of treatment significantly (P<0.05) increased hepatic glycogen level. On the other hand after 14 days of treatment lipid profile cholesterol (CHOL), high density lipoprotein (HDL), triglyceride (TG), low density lipoprotein (LDL), very low density lipoprotein (VLDL) were significantly (P < 0.05) improved in diabetic rats treated with Tamarindus indica seeds extracts. The results suggested that the both hydro-alcoholic and aqueous extracts of Tamarindus indica seeds possess potential antidiabetic, hypolipidemic effect.